Factors Causing Stunting In Toddlers Aged 0 To 5 Years In Coastal Communities - Nurhayati, Nurhayati; Hutasuhut, Khofifa Zuriah Tsani; Rahmi, Fathul; Siregar, Widya Anggraini; Saraan, Astuti; Dalimunthe, Halimatus Sa’diyah (International Journal Labs, 2023)
In Indonesia, Stunting is a current issue with nutrition. About one in four children worldwide has stunted growth or stunting. When the nutritional status of a child is assessed using length, whether height and their z-score is below the WHO-MGRS (Multicentre Growth Reference Study) criteria in 2005, they are considered short toddlers. Children with z-score -3SD or lower are considered as very short toddlers. This study set out to identify the contributing causes to stunting in coastal areas. Quantitative research is the chosen research methodology. This type of study was conducted in the working space of Posyandu cadres in the village of Sialang Buah for the coastal area. It is a cross-sectional study that uses analytical methods. Based on that findings It might be argued that the findings of our coastal community, specifically that village by Sialang Buah, does not now have stunting but is susceptible to it. In Sialang Buah Village, toddlers are at risk for stunting because the mother's level of education is low, that parents' level on labor there is low, which results in less income.